RCM‐E simulation of a thin arc preceded by a north‐south‐aligned auroral streamer. Issue 8 (16th April 2014) - Yang, Jian; Toffoletto, Frank R.; Wolf, Richard A.
Abstract The Time History of Events and Macroscale Interactions during Substorms (THEMIS) all‐sky imager data have recently revealed a repeatable sequence that occurs during many auroral substorms, in which a newly formed thin arc is preceded by an equatorward propagating streamer. The paper aims at modeling this sequence using the Rice Convection Model–Equilibrium. The simulation shows a thin arc arising when a plasma sheet bubble with its PV5/3 reduced to the transition region value arrives at the magnetic transition region. The modeled thin arc consists of two parts: the one east of the streamer is the result of the bubble pushing high PV5/3 flux tubes ahead of it, strengthening the upward region 2 current, and the one west of the streamer is associated with westward drifting bubble particles, sliding along the transition region. The model predicts that (1) the westward and eastward leading edges of the thin arc propagate azimuthally at a speed of ~0.5–2.7 km/s and (2) the streamer‐induced thin arc is accompanied by classic signatures of bubble injections.